HUBUNGAN KEARIFAN LOKAL DAN KURIKULUM BERBASIS CINTA DENGAN PENGUATAN MODERASI BERAGAMA DALAM PENDIDIKAN AGAMA ISLAM - Jami’atul Husna; Ahmad Zainuri; Mukti Ali; Muhamad Fauzi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to deeply analyze the synergy between local wisdom and the implementation of a love-based curriculum in strengthening religious moderation in Islamic Religious Education (PAI) environments. Amid increasing ideological polarization and religious exclusivism, a more humanistic and contextual pedagogical approach is needed. However, previous research tends to examine local wisdom, educational curriculum, and religious moderation separately, thus failing to produce an integrative model capable of connecting the cultural and affective dimensions in PAI learning. This study uses a descriptive qualitative method with a library research approach. The results show that: (1) local wisdom functions as a sociocultural bridge that grounded universal Islamic values ​​(wasathiyah) in the local context; (2) a love-based curriculum transforms the learning process from merely knowledge transfer to an emancipatory process that prioritizes empathy and compassion; (3) the integration of the two creates an inclusive educational ecosystem, where religious moderation is not only cognitive material but also internalized in behavior. This study recommends a reorientation of the Islamic Religious Education (PAI) curriculum that integrates local wisdom values ​​and a pedagogy of compassion as a preventive strategy against radicalism.